Pyoderma gangrenosum in childhood - Kumar, A; Gurung, D; Pokharel, DB; Badal, KP; Jha, A; Parajuli, S (Journal of Institute of Medicine Nepal, 2008)
Case report: Pyoderma gangrenosum is a rare painful, necrolytic skin ulcer with an irregular undermined border. It is a part of the spectrum of neutrophilic dermatoses. We report a case of pyoderma gangrenosum in a twelve year old boy. The findings reported in the literature are also discussed. Key words: pyoderma gangrenosum, neutrophilic dermatosis, skin ulcer. The full text of this paper is available at Journal of Institute of Medicine website